Comparison of omega-3 fatty acids and sulfasalazine in ulcerative colitis - Dichi, I; Frenhane, P.; Dichi, J. B.; Corrêa, Camila Renata [UNESP]; Angeleli, AYO; Bicudo, M. H.; Rodrigues, MAM; Victoria, C. R.; Burini, Roberto Carlos [UNESP] (Elsevier B.V., 2000)
Fish oil omega-3 fatty acids exert antiinflammatory effects on patients with ulcerative colitis. However, a comparative study in patients with mild to moderate ulcerative colitis receiving only sulfasalazine or omega-3 fatty acids has not been performed. We sought to detect changes in the inflammatory disease activity with the use of either fish oil omega-3 fatty acids or sulfasalazine in patients with ulcerative colitis. Ten patients (five male, five female; mean age = 48 +/- 12 y) with mild to moderate active ulcerative colitis were investigated in a randomized cross-over design. They received either sulfasalazine (2 g/d) or omega-3 fatty acids (5.4 g/d) for 2 mo. Disease activity was assessed by clinical and laboratory indicators, sigmoidoscopy, histology, and whole-body protein turnover (with N-15-glycine). Treatment with w-3 fatty acids resulted in greater disease activity as detected by a significant increase in platelet count, erythrocyte sedimentation rate, C-reactive protein, and total fecal nitrogen excretion. No major changes in protein synthesis and breakdown were observed during either treatment. In conclusion, treatment with sulfasalazine is superior to treatment with omega-3 fatty acids in patients with mild to moderate active ulcerative colitis. Nutrition 2000;16:87-901 (C) Elsevier B.V. 2000.
Keywords: ulcerative colitis; sulfasalazine; omega-3 fatty acids; disease activity indicators; protein metabolism; N-15-glycine